Incorporating an Earth Jurisprudence approach into South African environmental law for the protection of endangered species : options and challenges - Van Rooyen, Carla (Stellenbosch : Stellenbosch University, 2016)
Thesis (MPhil)--Stellenbosch University, 2016.